Using the Social Science Research Network to Aid and to Promote Research - Prebble, John; Caldwell, Julia; Keene, Amelia (Victoria University of Wellington Law Review, 2013)
The Social Science Research Network is a depository for academic scholarship. SSRN allows academic papers and abstracts to be accessible worldwide. Most papers may be downloaded from the SSRN database free of charge, but some links are to commercial sites. Posting papers to SSRN and subscribing to its site are not inherently complicated. However, it is possible for academic departments, particularly law schools, to use SSRN more efficiently and more flexibly than SSRN’s architects envisaged. For instance, one can establish a faculty working paper series with archived issues that are forever easily accessible, a much cheaper manner of establishing a working paper series than traditional ways, and a more permanent format than envisaged by standard SSRN systems. This article explains how SSRN works and how it can be used more effectively.